2021
DOI: 10.3390/hydrology8030134
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Impact of Climate Change on Surface Water Availability Using SWAT Model in a Semi-Arid Basin: Case of El Kalb River, Lebanon

Abstract: Assessing the impact of climate change on streamflow is crucial for depicting the vulnerability of water resources and for identifying proper adaptation measures. This study used the Soil and Water Assessment Tool (SWAT) to simulate the impact of climate change on the streamflow of El Kalb river, a major perennial river in Lebanon. The model performance was tested for monthly flow at two stations under a nine-year calibration period (2003–2011) and a four-year validation period (2012–2015). The model results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Compared with studies worldwide, this working temperature presents similar increases in future scenarios using the RCP 8.5. On the other hand, Saade et al (2021) studied the El Kalb River in a semiarid region. The study indicated that the average annual discharge of El Kalb River shortly (2021-2040) would decrease by around 28%-29% under the three RCP scenarios.…”
Section: Future Scenarios For 2030 2050 and 2100mentioning
confidence: 99%
“…Compared with studies worldwide, this working temperature presents similar increases in future scenarios using the RCP 8.5. On the other hand, Saade et al (2021) studied the El Kalb River in a semiarid region. The study indicated that the average annual discharge of El Kalb River shortly (2021-2040) would decrease by around 28%-29% under the three RCP scenarios.…”
Section: Future Scenarios For 2030 2050 and 2100mentioning
confidence: 99%
“…Hydrological modeling approaches, particularly the Soil and Water Assessment Tool (SWAT), have been used to tackle these shortcomings and to consider the impact of climate change on water discharge. Some research mentioned the wide application of the SWAT model for assessing the changes in water discharge under climate change conditions on a large watershed scale, such as Saade et al [9], Li and Fang [10], and Ougahi et al [11]. As mentioned in the climate change scenarios, the Ministry of Natural Resources and Environment of Vietnam published and updated these scenarios in the past (2009,2012,2016) and most recently in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…While others used the HMS model, and the results showed high correlation values [9][10][11][12][13]. In other studies, the ARC SWAT program was used to model surface runoff, and they obtained good evaluation coefficients for the results during the verification and testing stages [14,15].…”
Section: Introductionmentioning
confidence: 99%